Cytokine profiles in the detection of severe lung involvement in hospitalized patients with COVID-19: The IL-8/IL-32 axis. (March 2022) - Bergantini, Laura; d'Alessandro, Miriana; Cameli, Paolo; Otranto, Ambra; Luzzi, Simona; Bianchi, Francesco; Bargagli, Elena
Abstract: Coronavirus disease 2019 (COVID-19) is an infectious respiratory disorder caused by a new coronavirus called SARS-CoV-2. The pathophysiology of severe COVID-19 is associated with a "cytokine storm". IL-32 is a key modulator in the pathogenesis of various clinical conditions and is mostly induced by IL-8. IL-32 modulates important inflammatory pathways (including TNF-α, IL-6 and IL-1b), contributing to the pathogenesis of inflammatory diseases. Il-32 was never evaluated before in COVID-19 patients stratifying as mild-moderate and severe patients. A total of 64 COVID-19 patients, 27 healthy controls were consecutively enrolled in the study. Serum concentrations of biomarkers including IL-1β, IL-10, IFN-γ, TNF-α and IL-6 were quantified by bead-based multiplex analysis and Serum concentration of IL-8 and IL-32 were determined by enzyme-linked immunosorbent assay (ELISA) kits. Interestingly, among the blood parameters, neutrophil and lymphocyte counts were significantly lower in severe COVID-19 patients than in the other, on the contrary, CRP was significantly higher in severe patients than in other groups. The cytokines that best distinguished controls from COVID-19 patients were IL-8 and IL-32, while IL-6 resulted the better variables for discriminate severe group. The best model performance for severe group was obtained by the combination of IL-32, IL-6, IFN-γ, and CRP serum concentration showing an AUC = 0.83. A cut off of 15 pg/ml of IL-6 greatly discriminate survivor from death patients. New insights related to the cytokine storm in COVID-19 patients, highlighting different severity of disease infection.